The vest pocket guide to GAAP - Bragg, Steven M. (Wiley ; John Wiley [distributor], 2011)
Quick answers to your GAAP questions The Vest Pocket Guide to GAAP is the handy pocket problem-solver that gives today's busy financial executives the GAAP advice they need in a quick-reference format